Evaluación de desarrollo vegetativo de dos variedades de oryza sativa l. sembradas bajo el método Madagascar en CHEPÉN - LA LIBERTAD - Castillo Velásquez, Mayra Joseph (2016)
This research was conducted in the area Monte Verde, Chepén District, Chepén Province, Department of La Libertad since January 5, 2016 until March 8, 2016, with the aim of evaluating the vegetative development of two Rice varieties planted by Madagascar Method in Chepén - La Libertad. Evaluations were made touring the area "X", taking a plant at each point to be evaluated for a period of 3 months from when the plant was 11 days after transplantation, evaluated three times a week parameters plant height, leaf number on the main floor, tillering rate (average number of tillers per plant). According to the results it was found that the variety Tinajones has earlier age than the variety IR 43, since the eighth week that variety had already reached the point of cotton and variety IR 43 takes me two weeks to reach the point of cotton.